LEARNING TIME MANAGEMENT AND SELF-REGULATED LEARNING AS PREDICTORS OF STUDENTS' ACADEMIC CONSISTENCY IN THE 21ST CENTURY DIGITAL EDUCATION ERA - Luwiha, Luwiha; Taridi, Taridi; Andriyaningsih, Ayu; Suryanadi, Juni (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The 21st-century digital educational transformation demands that students possess high levels of adaptability amidst numerous technological distractions that can disrupt academic stability. Therefore, time management and Self-Regulated Learning (SRL) skills are vital instruments for maintaining sustained academic engagement. This study aims to analyze the relationship and predictive power of study time management and SRL on students' academic consistency in the digital education era. Using a quantitative approach with the Structural Equation Modeling (SEM) method, data were collected from 250 students at STIAB Jinarakkhita Lampung through proportional stratified random sampling. The analysis shows that study time management and SRL significantly predict academic consistency. Specifically, SRL was identified as the most dominant factor influencing consistency, while effective time management serves as a crucial foundation that strengthens students' self-regulation abilities. These findings confirm that academic consistency depends not only on internal motivation but also on technical skills in managing time resources. It is concluded that educational institutions need to integrate time management training and SRL strategies into their curricula to produce students who are resilient and adaptable to the challenges of the digital era. ABSTRAKTransformasi pendidikan digital abad ke-21 menuntut mahasiswa untuk memiliki kemampuan adaptasi tinggi di tengah banyaknya distraksi teknologi yang dapat mengganggu stabilitas akademik. Oleh karena itu, kemampuan manajemen waktu dan Self-Regulated Learning (SRL) menjadi instrumen vital untuk menjaga keterlibatan akademik yang berkelanjutan. Penelitian ini bertujuan untuk menganalisis hubungan dan daya prediksi manajemen waktu belajar serta SRL terhadap konsistensi akademik mahasiswa di era pendidikan digital. Menggunakan pendekatan kuantitatif dengan metode Structural Equation Modelling (SEM), data dikumpulkan dari 250 mahasiswa STIAB Jinarakkhita Lampung melalui teknik proportional stratified random sampling. Hasil analisis menunjukkan bahwa manajemen waktu belajar dan SRL secara signifikan menjadi prediktor konsistensi akademik. Secara spesifik, SRL teridentifikasi sebagai faktor yang paling dominan mempengaruhi konsistensi, sementara manajemen waktu yang efektif berperan sebagai fondasi krusial yang memperkuat kemampuan regulasi diri mahasiswa. Temuan ini menegaskan bahwa konsistensi akademik tidak hanya bergantung pada motivasi internal, tetapi juga pada keterampilan teknis dalam mengelola sumber daya waktu. Disimpulkan bahwa institusi pendidikan perlu mengintegrasikan pelatihan manajemen waktu dan strategi SRL ke dalam kurikulum untuk mencetak mahasiswa yang resilien dan adaptif terhadap tantangan era digital.